Integrative therapists’ subjective experiences and understanding of emotional connection in their practice - Luca, Maria; Andreou, Andros Luca (European Journal for Qualitative Research in Psychotherapy, 2019)
There is abundant literature on the therapeutic relationship and its importance, on relationality, and on the depth of empathy. Despite this, the experience of emotional connection in therapy from psychotherapists’ perspective, which is central to the development of the therapeutic relationship, is relatively scarce. There is little in the literature on how the therapist-client bond develops and how it helps clients. This study aimed to explore how integrative psychotherapists experience emotional connection and how in their view it develops. The study used hermeneutic phenomenological inquiry, specifically Interpretative Phenomenological Analysis (IPA). Semi-structured interviews were conducted with four integrative psychotherapists on their experience of emotional connection in their work with clients. It was found that the most influential conditions and therapist qualities that influence emotional connection from the therapists’ experience were: ‘Embodied, emotional openness’; ‘Empathy’; and; ‘Striving towards a therapeutic relationship’. These themes and their professional implications are discussed.